Chemical Profiles and Biological Activities of Microalga Chlorella sp. from Southeast Sulawesi - Haslianti, Haslianti; Asnani, Asnani; Fristiohady, Adryan; Sadarun, Baru; Sutariati, Gusti Ayu Kade; Sundowo, Andini; Yodha, Agung Wibawa Mahatva; Baharum, Syarul Nataqain; Idin, Sahidin (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
Microalgae Chlorella sp. grows in the seas of South-East Sulawesi, Indonesia. However, information on the chemical and pharmaceutical aspects of this species from this region is still limited. Therefore, this research aims to explore the chemical contents and biological activities of Chlorella sp. The sample was collected from the Kali Biru and Nambo waters, Kendari. The microalgae were isolated by the agar plating technique and extracted by ethanol. Chemical content was analyzed by phytochemical screening, Liquid Chromatography-tandem Mass Spectroscopy (LC-MS/MS), Total Phenolics Content (TPC) and Total Flavonoids Contents (TFC). Biological activities evaluation includes antioxidant, toxicity, cytotoxicity and antimicrobial. Antioxidant potency was evaluated by DPPH (2,2-diphenyl-1-picrylhydrazyl) radicals and ABTS (2,2’-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid). Toxicity and cytotoxicity properties were analyzed by BSLT (Brine Shrimp Lethality Test) and MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assays against Breast cancer (MCF-7) cell lines. Antimicrobial potency was tested towards E. coli, S. aureus and C. albicans. The result showed that ethanol extract of Chlorella sp. (EEC) contained phenolics, flavonoids, alkaloids and terpenoids/steroids which were supported by LC-MS/MS data, TPC and TFC with value 150.33 and 33.18 mgGAE.g-1 extract. Seven of ten identified major compounds caused this extract to have antioxidant and anticancer including xanthin, 1,1-Diethyl-3-oxo-2- triazanolate, Azelaic acid, ruspolinone, 6-keto prostaglandin F1a and glycol stearate. In general, the biological activity of EEC is less active than the positive controls for each assay. However, the EEC is more potential to be developed as antioxidant such as sunscreen and anticancer especially breast cancer with IC50 value 151-200 ppm and 100-500 ppm, respectively.